Territórios cercados, territórios esvaziados e conservação da natureza no oeste da província de Santa Cruz, Patagônia sul - Alejandro Fabian Schweitzer (Confins)
The implantation of the first protected areas in the Province of Santa Cruz is part of a strategy of effective occupation of the space by the national state, complementary to the implantation of the national territories and to the policies of settlement and colonization. The national parks located in the west of Santa Cruz, are among the first protected areas in Argentina. Since the 1930s, there has been a national enforcement authority, but only in 1980 with the creation of the National Parks Administration, the emptying of these spaces and the eradication of part of the pre-existing activities was imposed. Starting in the 1990s, land purchase and concentration strategies were deployed in large capitals, with the presence of banks and foundations that intervened in the expansion and creation of protected areas, fencing and emptying new spaces. This article seeks to contribute to a greater understanding of the processes of production of space and nature in peripheral spaces, the ways in which national and regional states organized conservation policies from the first protected areas to the current challenges for these spaces in the global scenario of hegemony of financial capital. To do this, the first section analyzes the evolution of the territory in relation to the implantation of protected areas and the current situation of conservation actions. In a second section, the strategies of the actors present in the territory and the material conditions for the maintenance and advancement of activities related to conservation are exposed. In conclusion, questions are raised about the conservation scenario and the guidelines of public policies, which range between support for the new dynamics of the conservation vacuum, the maintenance of the extractivist vacuum or attention to the basic needs of the population and the improvement of the life conditions.